Development of the Umayyad Civilization - Septri Larasati; Afrizal; Syawaluddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research describes the history of Islamic civilization during the Umayyad era. The aim of this research is to determine political, administrative and economic progress, as well as the causes of the decline and destruction of the Umayyad Bani. The study method used is literature study or library research by collecting various information related to the Umayyad civilization. Data collection with the results of previous research which supports the data in this research. The result was the Umayyah Dynasty, taken from the name of Umayyah bin 'Abdu Shams bin 'Abdu Manaf. The contribution of the Umayyad Dynasty's policies which had a positive impact on the development of Islamic civilization included: Political stabilization, thus opening up opportunities for development in various aspects of life, territorial expansion, infrastructure development, and the spread of Islamic da'wah. Meanwhile, the decline and destruction of the Umayyad dynasty was caused by many factors, including: the struggle for power between the royal family, the long-standing conflict with the Shiite and Khawarij opposition groups, the ethnic conflict between the North Arabian tribes and the South Arabian tribes, the incompetence of the caliphs in leading the government and the tendency of those who lived in luxury, the overthrow of the Bani Abbas who was fully supported by the Bani Hashim, the Shiites, and the Mawali group